Determinants of low bone mineral density in premenopausal polycystic ovary syndrome patients - YOLDEMİR, AHMET TEVFİK; YAVUZ, DİLEK (TAYLOR & FRANCIS LTD, 2017)
Objective: The aim of this study was to evaluate the bone mineral density (BMD) values and to determine the associations between BMD and insulin sensitivity, hyperandrogenemia, body mass index (BMI), and sex hormones in premenopausal polycystic ovary syndrome (PCOS) patients. Methods: A hundred and three women with PCOS and sixty age- and BMI-matched healthy control women were enrolled to this cross-sectional study. Serum androgen and estradiol (E2) levels were measured. Homeostasis model assessment of insulin resistance (HOMA-IR) and MATSUDA insulin sensitivity index (ISI) were calculated. BMD was measured with a dual X-ray absorptiometer. Results: Lumbar BMD (LBMD) and femoral neck BMD (FnBMD) values were significantly lower in PCOS group than controls [(p<0.01) and (p<0.01)]. In PCOS group, hyperandrogenemic women had higher LBMD and FnBMD values than normoandrogenemic PCOS patients [(p<0.01) and (p<0.01)]. In PCOS group, LBMD was significantly correlated with HOMA-IR (r=0.617; p<0.01), MATSUDA ISI (r=-0.665; p<0.01), serum E2 (r=0.488; p<0.01), total testosterone (r=0.436; p<0.01), and androstenedione (r=0.337; p<0.01) levels. Similar correlations observed for FnBMD. Conclusions: Despite the positive effects of hyperandrogenemia and hyperinsulinemia, PCOS patients have lower bone mineral density due to hypoestrogenism. Insulin resistance, BMI, estrogen, and androgen levels are the determinants of BMD in PCOS.
Keywords: Bone mineral density; HOMA-IR; hyperandrogenemia; MATSUDA; polycystic ovary syndrome; INSULIN-RESISTANCE; TESTOSTERONE LEVELS; BODY-COMPOSITION; LEAN WOMEN; HYPERINSULINEMIA; SENSITIVITY; HIRSUTISM